Aplicativo para alívio da dor crônica na coluna lombar em pessoas idosas - Montenegro, Cícera Patrícia Daniel (2020)
Introduction: Chronic non-communicable degenerative diseases of the spine result from the aging process and wear and tear of bones and soft tissues, providing muscle tension and pain. Guidance provided by trained professionals on how to relieve pain contributes to health promotion, disease prevention and consequent quality of life. Objectives: To identify scientific evidence on chronic low back pain in the elderly; to analyze the main complaints of low back pain and its implications in the daily activities of the elderly and to propose the construction of an application of guidelines for the relief of low back pain in the elderly. Method: This is a methodological, quantitative and qualitative study, structured in three stages: in the first, an attempt was made to identify scientific evidence from an integrative review with search for scientific articles in the Cumulative Index to Nursing and Allied Health Literature databases ( CINAHL), Scopus, Cochrane, Web of Science, Medical Literature Analysis and Retrievel System On-line (MEDLINE / PubMed) and in the Science Direct virtual library, using the indexed descriptors chronic pain, low back pain, aged, aged, 80 and over , Boolean operator and and Population, Interest and Context (PICo) strategy, from May to July 2020, with publication period from 2016 to 2020. The second stage was a field survey of 40 elderly people: 20 elderly people living in the area rural of Guarabira / PB and 20 from the urban area of João Pessoa / PB, who answered a semi-structured interview whose transcribed data were processed by the IRaMuTeQ software. In the third stage, it comprised the construction of a technological application of guidelines for the relief of low back pain in the elderly. Results and Discussion: The data obtained in the first stage comprised the analysis of 15 articles, classified into three thematic categories: descriptions of the aging process for the elderly; definitions of chronic low back pain and the influence of biopsychosocial aspects on low back pain in the elderly; such evidence demonstrates that the elderly recognize their functional limitations and value the treatment of the interdisciplinary team. In step two, the data obtained from the interviews and submitted to processing by the referred software indicated four categories: types of access to technology; digital inclusion in the daily lives of the elderly; activities predisposing to low back pain and resources to relieve pain, stressing that elderly people with a higher level of education handle the technological tools for guidance on prevention and health promotion more easily. The results obtained in the first two stages of the study supported the proposal to create the application Live without pain in the lumbar spine, in different languages, containing music, stretching and relaxation exercises, types of compresses and postural orientations. Final considerations: The results learned from this research supported the construction of an application containing audiovisual resources, facilitating the learning of the content and understanding of the guidelines, to be used as a tool in the relief of low back pain.